2015
DOI: 10.1007/s00192-015-2751-4
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and duration of response to botulinum neurotoxin A (onabotulinumA) as a treatment for detrusor overactivity in women

Abstract: Our results suggest that in patients who respond to onabotulinumA treatment, the duration of response declines after the fifth treatment, suggesting a possible tolerance effect and a subsequent decline in efficacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 19 publications
3
21
0
Order By: Relevance
“…In our study, therapeutic discontinuation occurred at 75.8 months on average, which corresponds to the data found in the literature . However, there is a discrepancy with the study by Chohan et al, which showed that BoNT‐A lost its efficiency by the fifth injection, with only 19.9% of patients pursuing the treatment after the fifth cycle.…”
Section: Discussionsupporting
confidence: 68%
“…In our study, therapeutic discontinuation occurred at 75.8 months on average, which corresponds to the data found in the literature . However, there is a discrepancy with the study by Chohan et al, which showed that BoNT‐A lost its efficiency by the fifth injection, with only 19.9% of patients pursuing the treatment after the fifth cycle.…”
Section: Discussionsupporting
confidence: 68%
“…Although improvements in the mean urinary frequency, incontinence, and urgency episodes continued to be significant at the 12th postoperative week and 9th postoperative month, improvements in the mean bladder and maximum volume capacities were no longer significant at the 9th postoperative month compared with the baseline. In most studies, the effects of a 100 U onaBoNT‐A injection were maintained for up to 11.1 months . Thus, we evaluated the efficacy, and the need for repeated injections through the 9th postoperative month.…”
Section: Discussionmentioning
confidence: 99%
“…Many second and third-line treatments for SUI and UUI have inconsistent outcomes, uncertain durability, and high risk of complications. 2122 For LUTS associated with benign prostatic hyperplasia (BPH), randomized clinical trials (RCT) have demonstrated the efficacy of commonly used pharmacologic therapies in men, but the beneficial effects of treatment may not be generalizable, can be costly because of long-term use, and produce numerous, often intolerable side-effects, which reduces adherence. 23 For interstitial cystitis/bladder pain syndrome (IC/BPS) and chronic prostatitis/chronic pelvic pain syndrome (CP/CPPS), numerous medical interventions have been proposed; however, effective treatment remains elusive.…”
Section: Challenges With Current Treatment Of Lutsmentioning
confidence: 99%